172k views
2 votes
Y = 4x - 6

2x - 3y = 8
If this problem is to be solved by substitution, which is a correct step?

A) 2x - 12x + 18 = 8
B) 2x - 12x - 18 = 8
C) 2x - 4x + 6 = 8
D) 2x + 12x + 18 = 8

User Garrows
by
5.2k points

1 Answer

0 votes

Answer:

B) 2x - 12x - 18 = 8

Explanation:

2x - 3y = 8

If y = 4x - 6, then substitute and solve:

2x - 3(4x - 6) = 8

2x - 12x - 18 = 8

10x - 18 = 8

10x = 8 + 18

10x = 26

x = 26/10

x = 2.6

y = 4(2.6) - 6

y = 10.4 - 6

y = 4.4

User Greg Chabala
by
5.0k points